Tinjauan Yuridis Tentang Perseroan Terbatas yang Tidak Menerapkan Wajib Vaksin Untuk Karyawannya - Putu Sekarwangi Saraswati; Ngurah Galang Jayadhifa (Kertha Wicaksana, 2022)
In studying the systematics of the existing legal substance, where we often hear of a legal subject in the substance of every existing policy, there are two legal subjects where there are Persons and Rechtpersoons, the focus of the author's research this time is on the rights and obligations of legal entities or rechtpersoons. itself in responding to a policy regarding mandatory vaccines that have appeared in a policy in the midst of the covid-19 pandemic in recent years, in responding to this the author wants to conduct research using normative juridical research methods in order to find out how broad this mandatory vaccine policy is in addressing legal subjects The existing method uses a positivist legislative approach with a law approach and a comparative approach. So it is felt that there is a need for a policy that the government can provide so that Covid-19 can be resolved optimally. The theoretical basis that the author uses is the Theory of Rule of Law, Theory of Justice, Theory of Benefit, the author does not escape the concept of a Limited Liability Company.